Modulation of Atlantic salmon miRNome response to sea louse infestation - Valenzuela-Muñoz, Valentina; Novoa, Beatriz; Figueras Huerta, Antonio; Gallardo-Escárate, Cristian (Developmental & Comparative Immunology, 2017)
12 pages, 7 figures MicroRNAs are non-coding RNA that plays a crucial role in post-transcriptional regulation and immune system regulation. On other hand, sea lice are prevalent parasites that affect salmon farming, generating different degrees of immune suppression depending on the salmon and sea louse species. Caligus rogercresseyi for example, which affects the salmon industry in Chile, decreases Th1 response, macrophage activation, TLR-mediated response and iron regulation in infected fish. In this study, we explore Atlantic salmon miRNome during infestation by C. rogercresseyi. Using small RNA sequencing, we annotated 1718 miRNAs for skin and head kidney from infected Atlantic salmon. The most abundant families identified were mir-10, mir-21, mir-30, mir-181 and let7. Significant differences were found between tissue, with 1404 annotated miRNA in head kidney and 529 in skin. Differential analysis of transcript expression indicated that at an early stage of infestation miRNA expression was higher in head kidney than in skin tissue, revealing tissue-specific expression patterns. In parallel, miRNA target prediction using 3′UTRs from highly regulated immune-related genes and iron metabolism showed that mir-140-4 and mir-181a-2-5 modulate the expression of TLR22 and Aminolevulinic acid synthase, respectively. This study contributes knowledge about the immune response of Atlantic salmon during infestation with sea lice This study was funded by CONICYT-Chile through the grants FONDAP (1510027), FONDECYT (1150077) and PCHA/Doctorado Nacional/2016–21161036 Peer reviewed